Systematics of Vitaceae in south America - Lombardi, Julio Antonio (Natl Research Council Canada-n R C Research Press, 2007)
In South America, the family Vitaceae is represented by 65 species divided into 2 genera: Cissus contains 64 species, whereas Vitis consists of only I species. Recent studies on the Neotropical Cissus reveal that with regard to species delimitation, trichome types and the morphology of fruits and seeds are more important than the traditionally used trichome density and leaf shape. Fifteen provisional species groups are recognized for South America, excluding one species whose grouping is uncertain. Future research in this area should incorporate other data (e.g., anatomical, histological, and molecular) to identify a subgeneric division in Cissus.